2016
DOI: 10.1080/15313204.2015.1131651
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Focused Brief Therapy With Latinos: A Systematic Review

Abstract: This article reviews all the published and non-published outcome studies that were randomized controlled trials (RCTs) or quasi-experimental designs on solution-focused brief therapy (SFBT) conducted with Latinos within the United States and Latin America. Data search included 18 databases for published articles, three databases for dissertations, and other sources of information. Forty-four studies met the criteria for a full-text review and, of those, six studies met criteria for this systematic review. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Prior research has shown that the average length of SFBT treatments is three to six sessions (Gonzalez et al, 2016; Kim et al, 2016), which is consistent with the length of BIs previously stated and other research indicating that commonly, individuals dropout from mental health treatment before the fifth session (Wells et al, 2013). Thus, we provided three individual sessions of SFBT to eight patients with AUDs.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Prior research has shown that the average length of SFBT treatments is three to six sessions (Gonzalez et al, 2016; Kim et al, 2016), which is consistent with the length of BIs previously stated and other research indicating that commonly, individuals dropout from mental health treatment before the fifth session (Wells et al, 2013). Thus, we provided three individual sessions of SFBT to eight patients with AUDs.…”
Section: Methodssupporting
confidence: 85%
“…The SFBT intervention can also be applied within primary care. From an exhaustive literature review prior this study, we learned that there are no linguistic adaptations of SFBT that have been implemented for AUDs in Latin America (González Suitt, Franklin, & Kim, 2016). Therefore, this study presents a pilot test of a linguistically adapted SFBT that is delivered by social workers in a primary care setting.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Concordante con ello es la adaptabilidad de la TBCS, la cual se ha implementado en diversidad de contextos y culturas (Gingerich & Peterson, 2013;González, Franklin & Kim, 2016;Kim et al, 2015), siendo adaptada para hacerla lingüísticamente pertinente en Chile sin perder sus componentes fundantes (González, Geraldo, Estay y Franklin, 2017), los cuales buscan relevar lo que es importante para el sujeto de intervención y fomentar la autodeterminación a través del reconocimiento de lo que ya funciona en su vida de Jong y Berg, 2012). Esto a su vez contribuye a brindar servicios de salud pública respetuosos con los derechos y la dignidad de las personas.…”
Section: Discusión Y Conclusionesunclassified
“…8,9 However, studies reveal that particularly in the university education period, students experience psychosocial problems, such as pessimism, insomnia, stress, anxiety in the face of challenges, which they encounter in their interpersonal relationships, and employ ineffective solution methods, such as letting everything happen and trying to calm down through crying. 10,11 Nursing education has a very compact education curriculum consisting of theoretical and practical processes, which leads students to have some hardships related to their educational activities as well as the difficulties experienced by them throughout their youth. 12 Specific incidents, such as information overload induced by both theoretical and practical courses, anxiety to harm the patient, concern over confronting with negative responses of patients and patient relatives, the necessity to make rapid decisions in case of the emergencies, challenges in the usage of medical instruments and apparatus, and the potentiality of encountering with the incidence of death, might lead to anxiety and interpersonal problems in students.…”
Section: Introductionmentioning
confidence: 99%
“…This diversity brings along the necessity to perform constructive roles in relationships between students, such as self‐knowledge, self‐control, assertiveness, self‐expression, and empathy 8,9 . However, studies reveal that particularly in the university education period, students experience psychosocial problems, such as pessimism, insomnia, stress, anxiety in the face of challenges, which they encounter in their interpersonal relationships, and employ ineffective solution methods, such as letting everything happen and trying to calm down through crying 10,11 …”
Section: Introductionmentioning
confidence: 99%